Gender and environment - Buckingham-Hatfield, Susan (Routledge introductions to environment series, 2000)
Accessible and lively, this is the first introductory level text to introduce the key issues in the rapidly growing area of gender and environment. This text provides an analysis of how gender relations affect the natural environment and of how environmental issues have a differential impact on women and men. Using case studies from the developed and developing worlds, this text covers · gendered roles in the family · community and international connections · conception · giving birth · western practices · the body and the self.
Keywords: 1900-1999; corps; environnement; famille; justice environnementale; maternité; projet charge mentale; périodes historiques; ressource en ligne; thématiques